IC 9334 Strategies For Improving The Effectiveness Of Human Resources - Robert H. Peters (The National Institute for Occupational Safety and Health (NIOSH), 1992)
This report presents a literature review conducted by the U.S. Bureau of Mines. The review summarizes what has been learned from the large volume of empirical studies on the effectiveness of eight types of interventions intended to increase organizational effectiveness via in the management of human resources. The interventions concern the following: recruitment, selection, training, objective feedback, goal setting, reward systems, participative management practices and organization development. Although many of these interventions appear to have the potential for improving the safety and efficiency of mining operations, it does not appear that they are being widely used. Examples are given of the successful use of a few of these interventions at mining operations. An analysis of the relationship between coal mine productivity and safety is also presented. This analysis generally supports the view that good safety performance and high productivity are NOT incompatible goals. In fact, safe mines also tend to be more productive and vice versa.